Lightning Deaths: A Retrospective Study Of Ten Years’ Period (2007-2017): Lightning Deaths - Ketenci, Hüseyin Çetin; Altınok, Mehmet; Çakır, Emel; Aydoğdu, Halil ilhan; Beyhun, Nazım Ercüment (The Bulletin of Legal Medicine, 2021)
Introduction: Lightning is a major reason of weather-related deaths and injuries. The risk of being struck by lightning is higher in those who work outdoors. Methods: A retrospective study of 19 lightning-related deaths that obtained from the archives of ... were evaluated between 2007-2017. Information on demographics, circumstances, presence of the other injured or dead creatures at the scene, witness statements, information sent by judicial authorities about place of the event, external examination of autopsy, presence of visceral organ damage, and histopathological - toxicological findings were collected and analyzed. Results: The age range of the cases was between 8-75 years and 15 of them are males. 9 of the cases were shepherd. The number of the cases peaks in June with 9 cases. 17 of the decedents were found in outdoor spaces. On the external examinations of 8 cases (42%) had Lichtenberg figure. The electrical entrance regions were head and neck in 10 cases (53%). Bleeding, contusions and lacerations, especially in the lungs and brain, were considered to be due to the blast effect of the lightning. Subepidermal blistering, elongation of the epidermis and dermis cell, intraepidermal vesicles and collagen denaturation were found during histopathological examinations. Conclusions: Lightning is an airborne event that can cause death in outdoor environments. Lichtenberg figure, macroscopic bleeding in the lungs and brain, and subepidermal blisters in histopathology may be found during forensic examinations. Awareness trainings should be provided for the risks of lightning strikes in the society.